Pós reveladores nas impressões papilares latentes e suas variações - GERAHRDT, Daniel de Almeida (2023)
The developing powders have become an interesting line of research on technical-scientific details around the identification through genetic profiles related to the remnants present in latent papillary prints. The present work aims to gather, through a brief literature review and present the most commonly used types of powders, disclose and detail characteristics presented from factors that influence its adherence. Several factors are of paramount importance such as the purity and chemical nature of the powder-printed papillary ridge components to define whether the development has a satisfactory result. Thus, it is possible to state that the energetic variation between the adhesive and cohesive forces at the printed papillary post-crest interface is directly linked to intermolecular interactions, and other components of this interface, such as surface free energy and wettability. The present work aims to compare the revealing powders cited in the literature in the last 10 (ten) years, aiming at exposing their characteristics, methodologies of use and classification of the most used materials.